LAND USE AND LAND COVER DYNAMICS IN MUNICIPALITIES OF THE UPPER PARAGUAY RIVER BASIN BASED ON THE GEOPORTAL TERRACLASS - Esquerdo, Júlio César Dalla Mora; Antunes, João Francisco Gonçalves; Coutinho, Alexandre Camargo; dos Santos, João Luis; Terra Parizzi, Talita Nogueira; Bertolo, Lídia Sanches (Ra'e Ga: o Espaço Geográfico em Análise, 2019)
The Upper Paraguay Basin (hereafter, by the Portuguese acronym BAP) has great ecological importance to Brazil since it includes the Pantanal, one of the largest wetlands in the world. Monitoring the land use and the land cover (LULC) is strategic not only for the floodplain of BAP but also for its plateau since the floods in Pantanal are affected by the actions conducted in its surroundings. Part of the BAP area placed within the State of Mato Grosso is mapped by the TerraClass Amazon Project and, therefore, the LULC dynamics in these localities can be assessed through these official data. The aim of this study was to analyze the LULC dynamics in three municipalities in the State of Mato Grosso, Brazil, using the geospatial tools provided by a Web-GIS based on data from the TerraClass Amazon Project. The results showed that in the municipalities of Denise and Barra do Bugres, between 2004 and 2014, there was a significant increase in the areas of Semi-Perennial Agriculture mainly due to the conversion from Cultivated Herbaceous Pasture. In the municipality of Santo Afonso, the class that presented the highest growth rate in the period was Annual Agriculture, with most of the areas being converted from pasture areas. The results highlight the processes of territorial dynamics that took place in the studied municipalities. The conversion from cultivated pasturelands to croplands (annual or semi-perennial agriculture) has been the main responsible aspect for the expansion of the agricultural activity in these municipalities.